First record of piebaldism in Corynorhinus townsendii and mass occurrence of atypical coloration in cave-dwelling bats in Northern Mexico: Atypical coloration of cave bats - Rivera Villanueva, Aquetzalli Nayelli; Kidoguchi, Hiroya; Guzmán-Velasco, Antonio (Therya Notes, 2026)
Chromatic disorders are phenotypically aberrant pigmentation in the skin, fur, or other parts of the integumentary system. More research is needed to understand the prevalence, causes, and consequences of atypical coloration in mammals. In bats, chromatic anomalies are reported globally, but regions such as Northern Mexico remain underrepresented or lacking any data altogether. To start exploring the ecology of atypical coloration in bats, we recorded the number of bats presenting atypical coloration and its prevalence by setting mist nets to capture bats. Also, as supplementary information, the number of bats detected in each cave with an infrared video camera was recorded. This study was conducted in two caves: Santa Catarina Cave in Nuevo León and Muzquiz Cave in Coahuila, Mexico. We recorded the prevalence of atypical coloration, sex, reproductive stage, and age of all the captured bats. Here we report high levels of occurrence of atypically colored Tadarida brasiliensis, as well as the first report of piebaldism in Corynorhinus townsendii. The prevalence of atypical coloration as a white collar in T. brasiliensis in Santa Catarina cave ranged from 0% in August 2023 up to 86.46% in May 2024. For the Muzquiz cave, the prevalence of atypical coloration was 0.17% on December 13th-14th, 2024, with one bat. To our knowledge, this is the first study to report a mass occurrence of atypical coloration that incorporates population composition data about atypically patterned bats in Latin America, including an estimation of the number of bats in the caves and prevalence of atypical coloration. We propose that the next steps for studies on atypical coloration in bats should record as much data as possible when these cases are encountered, with at least data about their age, reproductive stage, and behaviour.